The human U1 snRNA promoter and enhancer do not direct synthesis of messenger RNA. - Dahlberg, J E (1988)
We examined the ability of the 5' flanking region sequences of a human U1 RNA gene to direct synthesis of functional mRNA. When fused to chloramphenicol acetyltransferase (CAT) coding region sequences, the upstream sequences of the U1 gene were able to stimulate the synthesis of functional CAT mRNA in 293 cells but not in HeLa cells. Most of the polyadenylated CAT mRNA in 293 cells originated from cryptic promoters in the upstream U1 sequences, but nearly all of the CAT-specific RNA originating at position +1 (relative to the U1 gene promoter) was non-polyadenylated; this confirmed that the bona-fide U1 gene promoter was unable to direct efficient synthesis of poly-A+ mRNA. Our results demonstrate that the snRNA gene promoter and enhancer elements, although very efficient in transcription of snRNAs, are unable to direct transcription of polyadenylated mRNAs. However, other sequences in the 5' flanking region of the human U1 gene can activate transcription of functional mRNA, with 5' ends upstream of the normal transcription start site.